INFLUENCE OF ECO-FRIENDLY POST HARVEST TREATMENTS ON PULP CHROMA AND HUE ON MANGO CV. ALPHONSO FRUITS - NETRAVATI; S.L. JAGADEESH; G. J. SURESHA; G. S. K. SWAMY (The Bioscan, 2015)
The effect of post-harvest treatments on instrumental chroma value and hue angle of mango (cv. Alphonso) fruit pulp was studied. Green and mature mango cv. Alphonso fruits were subjected to various prestorage treatments viz., hot water, chitosan, Aloe vera gel, salicylic acid, boric acid and azoxystrobin, Solanum nigrum leaf extract and Trichoderma harzianum. The fruits were surface dried and placed in corrugated fibre board boxes and cold stored (13±1oC) for 4 weeks and in ambient condition for 1 week. The treated mango fruits did not alter much chroma and hue angle values as compared to untreated fruits throughout the storage period. Mango fruits dipped in hot water for 50-55°C for 5 minutes recorded minimum changes in C* (45.68) followed by 1 % chitosan treatment for 1 minute (48.01) as compared with control (62.01) after 28+7 days of storage. Similarly, a minimum change in h° (10.22) was in chitosan treatment. In conclusion, hot water and chitosan treatments were effective in maintaining the pulp color, indicating the reduced ripening process and extended storage life of mango cv. Alphonso fruits.